Pengaruh likuiditas, leverage, ukuran perusahaan, dan profitabilitas melalui kebijakan dividen terhadap nilai perusahaan pada perusahaan sektor infrastruktur, utilitas, dan transportasi - Rohmatulloh, Arjun (Jurnal Ilmu Manajemen, 2023)
This research aims to examine the influence of liquidity, leverage, firm size, profitability, and dividend policy on firm value, as well as to determine the impact of profitability on firm value through the mediation of dividend policy in infrastructure, utilities, and transportation companies listed on the Indonesia Stock Exchange (IDX) from 2017 to 2021. The data used in this study are quantitative data obtained from secondary sources. The population of this research consists of infrastructure, utilities, and transportation companies listed on the Indonesia Stock Exchange from 2017 to 2021. The sampling technique used is purposive sampling, resulting in a sample size of 14 companies. The data were analyzed using the multiple linear regression and sobel test for the mediation effect. The research findings indicate that leverage, as proxied by the debt-to-equity ratio, has a significant and positive effect on firm value. However, liquidity (current ratio), firm size, profitability (return on assets), and dividend policy (dividend payout ratio) do not have a significant influence on firm value. Additionally, dividend policy does not mediate the relationship between profitability and firm value. Therefore, infrastructure, utilities, and transportation companies during the period of 2017 to 2021 should focus on managing leverage and debt to improve company performance and profitability. By effectively managing their debt, these companies can instill investor confidence and enhance their overall performance, ultimately leading to increased firm value.